(3GdafOGb aj GdHfOGbs - (3CMeO Hf eMeO GdeOfjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhHYO bhd GdSGFd Yf SDGd HYV GdeNGdajf Ch cdge Hbhdg bGd Gdgd JYGdi (B:" (3hYdefGg UfYI dHhS dcf dJMUfce ef HCSce? aeG HGd GdOQhY GdBf dGJMUf ef HGSe GdHfOb s
(3BNQgG (B:s
(3aKHJ GdbOe dPGJg hUaGJg hGdMeO ddg QH GdYGdejf EfJgJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdCNjQIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedc SfI (B1215 (3HGSe YHO GdMajX eTMhfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds